Assessment of sediment toxicity in the Lagoon of Venice (Italy) using a multi-species set of bioassays - PICONE, Marco; Bergamin, Martina; LOSSO, Chiara; Delaney, Eugenia; ARIZZI NOVELLI, Alessandra; VOLPI GHIRARDINI, Annamaria (Ecotoxicology and Environmental Safety, 2016)
Within the framework of a Weight of Evidence (WoE) approach, a set of four toxicity bioassays involving the amphipod Corophium volutator (10 d lethality test on whole sediment), the sea urchin Paracentrotus lividus (fertilization and embryo toxicity tests on elutriate) and the pacific oyster Crassostrea gigas (embryo toxicity test on elutriate) was applied to sediments from 10 sampling sites of the Venice Lagoon (Italy). Sediments were collected during three campaigns carried out in May 2004 (spring campaign), October 2004 (autumn campaign) and February 2005 (winter campaign). Toxicity tests were performed on all sediment samples. Sediment grain-size and chemistry were measured during spring and autumn campaigns. This research investigated (i) the ability of toxicity tests in discriminating among sites with different contamination level, (ii) the occurrence of a gradient of effect among sampling sites, (iii) the possible correlation among toxicity tests, sediment chemistry, grain size and organic carbon, and (iv) the possible occurrence of toxicity seasonal variability. Sediment contamination levels were from low to moderate. No acute toxicity toward amphipods was observed, while sea urchin fertilization was affected only in few sites in just a single campaign. Short-term effects on larval development of sea urchin and oyster evidenced a clear spatial trend among sites, with increasing effects along the axis connecting the sea-inlets with the industrial area. The set of bioassays allowed the identification of a spatial gradient of effect, with decreasing toxicity from the industrial area toward the sea-inlets. Multivariate data analysis showed that the malformations of oyster embryos were significantly correlated to the industrial contamination (metals, polynuclear aromatic hydrocarbons, hexachlorobenzene and polychlorinated biphenyls), while sea urchin development to sediment concentrations of As, Cr and organic carbon. Both embryo toxicity tests were significantly affected by high ammonia concentrations found ...